COMP-07. COMPARATIVE MOLECULAR LIFE HISTORY OF SPONTANEOUS CANINE AND HUMAN GLIOMA. (5th November 2018) - Amin, Samirkumar; Boudreau, Beth; Martinez-Ledesma, Juan Emmanuel; Anderson, Kevin; Kim, Hoon; Johnson, Kevin; Dickinson, Peter; Packer, Rebecca; Taylor, Amanda; Rossmeisl, John; Heimberger, Amy; Levine, Jonathan; et al.
Abstract: Sporadic glioma occurs in companion dogs at frequencies comparable to humans. Genomic characterization of canine glioma has a distinct merit, in that age distribution at the time of diagnosis implies a pediatric disease while the animals are in the adult stage of life. This creates an opportunity to compare relative timing of driver events to that of human glioma, and to evaluate the importance of host context in the presence of driver alterations. Second, breed-specific elevated cancer risk enables increased sensitivity to the characterization of evolutionary conserved mammalian mutational processes in gliomagenesis. We performed whole genome, exome, transcriptome and methylation sequencing on 188 canine tumor and germline samples. As in human adult gliomas, we found frequently occurring alterations in Tp 53 pathway, cell cycle pathway ( Cdk4, Cdkn2a ), and receptor tyrosine kinases ( Egfr, Pdgfr α) in canine glioma. Common R132 mutations in the Idh1 gene reflected a remarkable and species-agnostic but cancer-specific driving effect. Frequent whole chromosome gains were observed in syntenic regions of chromosome 13, harboring Pdgfr α and Myc, but we found notable absence of 1p/19q co-deletion and Tert promoter mutations. We calculate mutational processes and highlight ones related to DNA damage repair and transcriptional strand bias in both species. We also estimate mutational rate and relative timing of mutations, and compare those to human glioma in mapping life history of glioma, i.e., are canine glioma more similar to adult or pediatric human glioma? We found coding mutation rate on the lower end of human adult glioma cases but with a broader spectrum (0.3–3 per MB), while subset of cases having mutations found in human pediatric cancer drivers, e.g., Kmt2c, Setd2, Bcor. In bringing together a large canine glioma genomic sequencing dataset and comparing to human glioma, our study provides unique insights into glioma etiology and the chronology of glioma-causing somatic alterations.